Pengaruh Insektisida Berbahan Aktif Abamektin 18 g/l terhadap Struktur Komunitas Predator Wereng pada Tanaman Padi (Oryza Sativa L.) (Graminae) - I MADE SUTIAWAN; A.A AYU AGUNG SRI SUNARI; I KETUT SUMIARTHA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Influence of Insecticide With an Active Ingredient Abamektin 18 g/l against Community Structure of Planthopper and Leafhopper Predator on Rice (Oryza sativa L.) (Graminae) This research was conducted in Buwit Village, Kediri District, Tabanan Regency, from September until November 2017. The purpose of this research is to know the effect of insecticide with active ingredient Abamektin 18 g /l to diversity, abundance, dominance and functional relationship of predator to Planthoppers and Leafhoppers on ricefield. The study used Randomized Block Design (RBD) with 5 treatments (2,00 cc/l; 1,50 cc/l; 1,00 cc/l; 0,50 cc/l; 0 cc/l) with 5 replications. The result of this research showed that insecticide with active ingredient Abamektin 18 g /l have significant effect to diversity and abundance of predator popolation with low predator diversity index. Abundance of predator populations showed significant differences between control and treatment on all nine types of predators founded. Insecticides with active ingredient Abamektin 18 g/l have a significant effect on predator domination. From the nine types of predators founded, in general Paederus fuscipes most dominance. Lycosa pseudoannulata is the most effective predator in controlling planthopper pests that have a strong functional relationships with plant hopper pests.